The Influence Of Electronic Word Of Mouth And Celebrity Endorsment On Thepurchasing Decision Process Of “Emina” - Tresnareta Budiman; Hapitalia H; Rohimat Nurhasan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2023)
This study aims to determine and analyze the effect of electronic word of mouth and celebrity endorsement on the purchasing decision process for Emina brand cosmetic products for millennial consumers, through social media in Garut Kota District. The data used in this study are primary data, the results of distributing questionnaires to 100 respondents of millennial age, born in 1981-2000 in Garut City District, using non-probability sampling and accidental sampling techniques. The independent variables in this study are electronic word of mouth (X1) and celebrity endorsement (X2), while the purchasing decision process is placed as the dependent variable (Y). Hypothesis testing was carried out using Structural Equation Modeling (SEM) PLS with the help of Smart PLS software version 3. The results showed that electronic word of mouth has a positive effect on the decision process to purchase Emina cosmetics for millennial consumers, through social media. Celebrity endorsement has a positive effect on the decision process for purchasing Emina cosmetics for millennial consumers through social media. Thus it can be concluded. that if the electronic word of mouth reviews are getting better or have a positive value, it will have a positive influence on the consumer purchasing decision process for Emina cosmetics, and if the celebrity endorsement is more attractive, or more popular, it will have a positive effect or encourage the Emina cosmetics purchasing decision process